Characteristics Of Phytases From Soybeans And Microorganisms Involved In The Tempe Production - Sutardi .; K A Buckle (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2004)
Tempe was prepared from Forest variety of soybeans inoculated with pure culture of the mould Rhizopus oligosporus strain CT11K2. Partially purified phytases from soybeans, mould of the R. oligosporus strain CT11K2, yeasts (Endomycopsis burtonii, Candida diddensiae and Candida tropicalis) and bacteria (Streptococcus faecium and Streptococcus dysgalactiae) involved during tempe production were prepared according to procedure developed by Sutardi (1988). The crude phytases were characterized and phytic acid, inorganic and total phosphorous content of soybeans, intermediate products and tempe, were also determined. Results show that phytases, produced by microorganisms involved in tempe production, and by endogenous soybean phytase, had significantly different characteristics especially on optimum pH, temperature and substrate, Km and Vmax values, inactivation and activation energy and also temperature coefficient. All phytases contribute to the reduction in phytic acid content; and mould phytase, especially the extra-cellular enzyme, and the endogenous soybean phytase, showed the dominant effect on phytic acid degradation compared with other microbial phytases and physical treatments such as soaking, boiling and steaming. Phytic acid content of soybeans was reduced by more than 50% from about 10.4 to about 4.9 – 5.0 mg/g (DWB) in fresh tempe (after 40 h fermentation at 30oC). Key words: Characteristics, pytase, soybeans, microorganisms, tempe.